Tributyltin-resistant bacteria from estuarine and freshwater sediments. - Wuertz, S (1991)
Resistance to tributyltin (TBT) was examined in populations from TBT-polluted sediments and nonpolluted sediments from an estuary and from fresh water as well as in pure cultures isolated from those sediments. The 50% effective concentrations (EC50s) for populations were higher at a TBT-polluted freshwater site than at a site without TBT, suggesting that TBT selected for a TBT-resistant population. In contrast, EC50s were significantly lower for populations from a TBT-contaminated estuarine site than for those from a site without TBT, suggesting that other factors in addition to TBT determine whether populations become resistant. EC50s for populations from TBT-contaminated freshwater sediments were nearly 30 times higher than those for populations from TBT-contaminated estuarine sediments. We defined a TBT-resistant bacterium as one which grows on trypticase soy agar containing 8.4 microM TBT, a concentration which prevented the growth of 90% of the culturable bacteria from these sediments. The toxicity of TBT in laboratory media was influenced markedly by the composition of the medium and whether it was liquid or solid. Ten TBT-resistant isolates from estuarine sediments and 19 from freshwater sediments were identified to the genus level. Two isolates, each a Bacillus sp., may be the first gram-positive bacteria isolated from fresh water in the presence of a high concentration of TBT. There was a high incidence of resistance to heavy metals: metal resistance indices were 0.76 for estuarine isolates and 0.68 for freshwater isolates.(ABSTRACT TRUNCATED AT 250 WORDS)